Linguistic diversity and accessibility in Mexican government web sites: executive branch - Pérez Salazar, Gabriel; Aguilar Edwards, Andrea; Mata Martínez, Cynthia Nallely (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
In Mexico, linguistic diversity is a right protected by various initiatives and laws. However, the ethno-linguistic mosaic found in Mexico due to the multicultural nature of the population, has not been properly addressed by online public policies. This study presents an assessment of the indigenous language provision on Mexican government websites at a federal, state and local level. Its principal results show that practically no indigenous-language content is available on such e-Government sites, and highlight accessibility issues in some State Governments. This leaves the Mexican indigenous population in a situation of great inequality that poses a huge threat to their information access rights.